Drivers of competitive entrepreneurial families in the Eastern Cape, South Africa - Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
There is global acceptance that the growth and sustainability of entrepreneurship initiatives is central to national development and hence the search for strategies to boost the growth of entrepreneurship across regions is crucial. Despite these initiatives in countries such as South Africa small enterprises remain fragile and have a high failure rate making the need for accelerated efforts to boots entrepreneurship a priority. In this regard, the purpose of this study was to explore the drivers or enablers of family entrepreneurship. Families were of interest in this study owing to their centrality in societal development. The study adopted the qualitative approach that was based on the use of focus group discussions with some family entrepreneurs in the eastern Cape in order to explore their perspectives on the drivers of competitive family entrepreneurial ventures. The study found that there are community based, government induced as well as socio cultural and context specific enablers for family enterprise competitiveness in the Eastern Cape. These enablers are facilitated by an appropriate vision for strengthening families, value for indigenous systems, adoption of context specific strategies for entrepreneurship development. It is recommended that government policy on family entrepreneurship should be strengthened given the potential of family entrepreneurship to improve entrepreneurial activity in South Africa.